Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

For a certain problem, I am trying to solve the ODE $$\ddot{z}(t) - \omega^2 z(t) = f_0 \Big(e^{-i(\omega+\delta)t}+e^{-i(\omega-\delta)t}\Big)$$ where $\omega$ is a real and $\delta$ is close to zero. I am pretty clueless what to do here, any hint would be appreciated.

share|cite|improve this question
up vote 4 down vote accepted

This is just to tell you that there is a general formula to solve the EDO

$$y''+ay'+by=f(t),\quad y(t_0)=y_0,\ y'(t_0)=y_1.$$

I'll try to derive the formula as naturally as possible (without claiming to prove anything).

First put the above EDO in the form


where $\alpha$ and $\beta$ are complex numbers. The remainder of the euclidean division of a polynomial $P(X)$ by $(X-\alpha)(X-\beta)$ is

$$\begin{cases}\displaystyle P(\alpha)\ \frac{X-\beta}{\alpha-\beta} +P(\beta)\ \frac{X-\alpha}{\beta-\alpha}&\text{if }\alpha\not=\beta\\ \\ P(\alpha)+P'(\alpha)\ (X-\alpha)&\text{if }\alpha=\beta. \end{cases}$$

If you replace formally $P(X)$ by $e^{tX}$ in the above expressions, you get

$$\begin{cases}\displaystyle e^{\alpha t}\ \frac{X-\beta}{\alpha-\beta} +e^{\beta t}\ \frac{X-\alpha}{\beta-\alpha}&\text{if }\alpha\not=\beta\\ \\ e^{\alpha t}+t\ e^{\alpha t}\ (X-\alpha)&\text{if }\alpha=\beta. \end{cases}$$

If you write this polynomial in the form $g_0(t)+g_1(t)\ X$, you get

$$g_0(t)=\begin{cases}\displaystyle\frac{\alpha\,e^{\beta t} -\beta\,e^{\alpha t}}{\alpha-\beta}&\text{if }\alpha\not=\beta\\ \\ (1-\alpha\,t)\,e^{\alpha t}&\text{if }\alpha=\beta, \end{cases}$$

$$g_1(t)= \begin{cases} \displaystyle\frac{e^{\alpha t}-e^{\beta t}}{\alpha-\beta}&\text{if }\alpha\not=\beta\\ \\ t\,e^{\alpha t}&\text{if }\alpha=\beta. \end{cases}$$

Let $\alpha,\beta,y_0,y_1$ be complex numbers, let $t_0$ be a point in some open interval $J$, and let $f:J\to\mathbb C$ be continuous. Then the solution to

$$y''-(\alpha+\beta)\,y'+\alpha\,\beta\,y=f(t),\quad y(t_0)=y_0,\ y'(t_0)=y_1$$


$$y(t)=y_0\ g_0(t-t_0)+y_1\ g_1(t-t_0)+\int_{t_0}^tg_1(t-x)\,f(x)\ dx.$$

EDIT. Here is the (unrequested) solution to the general order $n$ linear ODE with constant coefficients.

Let $P$ be a degree $n>0$ monic complex polynomial in the indeterminate $X$, let $f$ be a continuous function on the real line, and let $y_0,\dots y_{n-1}$ be complex numbers. The solution to the ODE

$$P(d/d t)\ y=f(t),\quad y^{(k)}(0)=y_k\quad(0\le k < n)$$


$$y(t)=\sum_{k=0}^{n-1}\ y_k\ g_k(t)+\int_0^t g_{n-1}(t-x)\ f(x)\ d x,$$ where the functions $g_k(t)$ can be computed as follows.

Put $P=\prod_{j=1}^r(X-\lambda_j)^{m(j)}$ and $Q:=\sum_{k=0}^ng_k(t)X^k$. Then $Q$ is obtained by solving, thanks to Taylor's Formula, the congruences

$$Q\equiv E_j\quad\bmod\quad(X-\lambda_j)^{m(j)},$$

for $j=1,\dots,r$, where we have set

$$E_j:=\exp(\lambda_jt)\ \sum_{r=0}^{m(j)-1}\ \frac{t^r}{r!}\ (X-\lambda_j)^r.$$

More precisely, we have

$$Q=\sum_{j=1}^r\ T_j\left(E_j\ \frac{(X-\lambda_j)^{m(j)}}{P}\right)\frac{P}{(X-\lambda_j)^{m(j)}}\quad,$$

where $T_j$ means "degree $<m(j)$ Taylor polynomial at $X=\lambda_j$".

share|cite|improve this answer

You can do by the method of variation of parameters.

Equivalently you can also directly do by the Green's function. The Green's function of the equation $$\frac{d^2z}{dt^2} - \omega^2 z = f_0 \left( e^{-i \left( \omega + \delta \right) } + e^{-i \left( \omega - \delta \right) }\right)$$ is $$G(t) = \frac{e^{\omega |t|}}{2 \omega}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.